Structural Transformation and Creativity Induced by Biological Agents during Fermentation of Edible Nuts from Terminalia catappa - Odutayo, Oluwatofunmi E.; Adegboye, Bose E. (Molecules, 2021)
: Terminalia catappa L. (tropical almond) is a nutritious fruit found mainly in the tropics. This study is aimed to establish the naturally biotransformed molecules and identify the probiotic agents facilitating the fermentation. The aqueous extracts from both the unfermented and fermented T. catappa nuts were subjected to gas chromatography/mass spectrometry (GC/MS) analysis. Syringol (6.03%), glutamine (1.71%), methyl laurate (1.79%), methyl palmitate (1.53%), palmitic acid (5.20%), palmitoleic acid (2.80%), and methyl oleate (2.97%) were detected in the unfermented nuts of the T. catappa. Additionally, two of these natural compounds (palmitic acid (4.19%) and palmitoleic acid (1.48%)) survived the fermentation process to emerge in the fermented seeds. The other natural compounds were biotransformed into 2,3-butanediol (1.81%), butyric acid (16.20%), propane-1,3- diol (19.66%), neoheptanol (2.89%), 2-piperidinone (6.63%), palmitoleic acid (1.18%), formamide, n-(p-hydroxyphenethyl)- (2.80%), and cis-vaccenic acid (1.69%) that newly emerged in the fermented seeds. The phytochemical compounds are likely carbon sources for the organisms facilitating the biotransformed molecules and product production. Four (4) potential probiotic bacteria strains, namely, Probt B1a, Probt B2a, Probt B4a, and Probt B4b, were isolated from the fermented nut. Enterococcus faecum, and Enterococcus faecalis were the organisms identified as driving the fermentation of the seeds. All strains were gram-positive, catalase-negative, and non-hemolytic, which suggests their harmless nature. N-(p-hydroxyphenethyl)-) was associated with fermentation for the first time, and neoheptanol was discovered as the main alcoholic molecule formed during the fermentation of the seeds. This fermentation is a handy tool for bio-transforming compounds in raw food sources into compounds with nutritious and therapeutic potentials.
Keywords: T. catappa; seed; nuts; food; processing; fermentation; Nigeria; Digital Development; Covenant University; ACE: Applied Informatics and Communication